The endogenous oxytocin system in depressive disorders: A systematic review and meta-analysis - Engel, Sinha; Laufer, Sebastian; Knaevelsrud, Christine; Schumacher, Sarah (Psychoneuroendocrinology, 2019)
The oxytocin system is involved in psychological functions and interacts with biological systems that are altered in patients suffering from depressive disorders. This suggests a possible role of oxytocin in the development and maintenance of depression. We provide the first systematic review and meta-analysis that specifically addresses differences in basal endogenous oxytocin concentrations between patients with depressive disorders and healthy controls. A systematic literature search was conducted to identify studies that measured basal endogenous oxytocin concentrations in depressive patients and healthy controls. We included k = 13 studies (n = 368 patients and n = 346 healthy controls) in the qualitative review and k = 9 studies (n = 273 patients and n = 273 healthy controls) in the meta-analytic procedure. Standardized mean group differences were non-significant (g = −0.02, CI = [−0.41; 0.36]), indicating that depressive patients and healthy controls did not differ in basal endogenous oxytocin concentrations. The overall effect was heterogeneous. Effects within studies showing comparable risks of biases, as rated according to the Newcastle-Ottawa Quality Assessment Scale, were non-significant as well, but homogeneous. The findings suggest that more complex research designs and methodological approaches should be employed to detect and understand a possible role of the oxytocin system in depressive disorders. We provide recommendations for subsequent promising study designs, involving the consideration of illness phase, comorbidities and correlations with psychological functions or symptoms. We point out the strengths of reactivity designs and multidimensional measurement approaches and recommend to linking future research questions to theories of depressio
Keywords: Oxytocin; Depression; Depressive disorder; Systematic review; Meta-analysis